Consumption replaces charity: Altruistic consumption behaviors and motivations targeting vulnerable groups—Research based on poverty alleviation consumption in China - Xin, Huiyu; Li, Chenzhuoer; Li, Wei; Wang, Hong; Liu, Ping; Li, Shouwei (Frontiers in Psychology, 2022)
Poverty alleviation consumption, which we call altruistic consumption, has become a new effective way to help vulnerable groups, but there are a few empirical researches on poverty alleviation through consumption. This article takes China's poverty alleviation actions as the research object, investigates and studies the relationship between altruistic consumption motivations and altruistic consumption behaviors that aim for vulnerable groups. It is found that altruistic consumption behavior is mainly affected by benefit group motivation, benefit morality motivation, benefit demander motivation, and benefit supplier motivation. There is a correspondence between the four altruistic consumption motivations and the four altruistic consumption behaviors. The strength of altruistic consumption motivations changes with changes in altruistic buying behavior. The strength of benefit group motivation decreases with the increase in the times of altruistic purchases, while the strength of benefit morality motivation, benefit demander motivation, and benefit supplier motivation increase with the increase in the times of altruistic purchases. Among the four kinds of altruistic consumption motivations that affect the times of altruistic purchases, the benefit demander motivation has a relatively greater influence. The results of this study have important guiding significance for vulnerable groups to formulating targeted proactive marketing strategies, preventing the altruistic consumption relationship dissolution, and realizing sustainable altruistic consumption.